The Italian Recession of 1993: Aggregate Implications of Microeconomic Evidence - Miniaci, Raffaele; Weber, Guglielmo (The Review of Economics and Statistics, 1999)
We use household-level data covering a ten-year period (1984 to 1993) to investigate the likely determinants of the Italian recession of 1993, the first year after WWII when private consumption fell. Consumption fell most for working-age households and for the self-employed. Our evidence is consistent with the response to permanent negative shocks due to the major pension reform of 1992 and the introduction of stricter tax-compliance measures for the self-employed. This is still true when we control for the role played by job losses and the collapse of the retail sector that characterized the early 1990s.